Comparison of open pancreatic necrosectomy with step-up minimally invasive approach as surgical treatment of patients with acute necrotizing pancreatitis - Khomiak, Ihor V.; Rotar, Oleksandr V.; Tereshkevych, Ivan S.; Rotar, Vasyl I.; Khomiak, Andrii I.; Taneja, Krishna Smriti (International Surgery Journal, 2017)
Background: Recent experimental and clinical researches improves our understanding of natural course of acute necrotizing pancreatitis and mechanisms of its complications development. Today there are no disagreements on the issue of timing and main indications for surgery of ANP, but different surgical approaches still exist. Methods: The analysis of treatment of 226 patients with acute necrotizing pancreatitis has been performed. The study group included 116 patients in whom consequently diapeutic methods, endoscopic and lumbotomic video-controlled pancreatic necrsequesterectomy, minilaparo and lumbotomy, in case of their insufficiency- “open” interventions on pancreas were applied. In 110 persons of the control group traditional surgical tactic with application of laparotomic procedures was used. Results: Sequential (step-up) implementation of mini-invasive surgery allowed to reduce the number of open wide operations by 3.4 times (p <0,05) and to postpone their performance: 85% of operations in the study group were performed after 4 weeks of the disease onset, in the control group only 33% (p <0,05). Compared with the control group the level of the first diagnosed OF after the surgery was significantly lower in patients undergoing preliminary mini-invasive surgery (12.5% versus 28.2%, p <0.05), the number of patients requiring prolonged intensive care after the surgery was significantly lower (17.5% versus. 38.2%, p <0.05). 4 patients of the study group died (versus 26 in the control group р<0,05). Conclusions: Application of step-up individualized approach in patients with acute necrotizing pancreatitis ensures a decrease in the number of laparotomic pancreatic necrosectomies and allows to postpone "open" operations for the period after the 4th week of disease onset which is accompanied by reduction of the incidence of postoperative organ failure and mortality.